Crime Discounting of Violent Victimization: The Role of Crime Type and Incident-Level Correlates - Muniz, Caitlyn N. (Crime & delinquency, 2024)
Many crime victims do not report their victimization and rates of reporting are disparate across crime types. While research has established victims are least likely to report sexual assault, less known is whether the crime discounting process affects reporting rates and whether this process differs by crime type. This paper thus examines reporting for robbery, sexual assault, and physical assault incidents, particularly exploring victims who indicated their incident was ?not a crime.? Using the National Crime Victimization Survey (n = 15,012) and a series of logistic regressions, this study found that, holding a number of incident-level correlates constant, crime type was the most salient predictor of reporting to police and nonreporting because the incident was ?not a crime.?